The Diatom Genus Navicula in Spring Ecosystems with the Description of Navicula aquaesuavis sp. nov - Cid-Rodríguez, María; Cantonati, Marco; Angeli, Nicola; Bilous, Olena; Al-Harbi, Maha; Lange-Bertalot, Horst; Levkov, Zlatko; Piana, Lucia; Spitale, Daniel; Saber, Abdullah A. (MDPI AG, 2024)
Given the limited understanding of species diversity and ecological preferences of diatoms of the genus Navicula in spring ecosystems, herein we present and describe as species new to science, Navicula aquaesuavis Lange-Bert., Levkov, Cid-Rodríguez, A.A.Saber and Cantonati sp. nov. This species was collected from a mountain spring located above the tree line at 1613 m a.s.l. in the Northern Apennines. The Fontana del Vescovo (Bishop’s spring), which is the locus classicus of the new species, has a low conductivity (60–70 µS cm−1), temperature of ca. 5 °C, circumneutral pH (7.3–7.5), relatively low nitrate (ca. 1 mg L−1), and also suffered from a discharge reduction from 1 to 0.1 L s−1 from 2011 to 2023. The putative new species was confirmed by a second finding in Northern Macedonia, and we thoroughly document this second population as well. We seized the opportunity to describe this new Navicula and review the global literature on the diatom genus Navicula in spring ecosystems. Using the results of this review and our own databases on springs and wells in central Europe and Egypt, we discuss the main Navicula species and their environmental preferences in spring habitats.
Keywords: diatoms; Navicula; springs; ecological preferences; distribution; new species